Activity and phylogenetic diversity of sulfate-reducing microorganisms in low-temperature subsurface fluids within the upper oceanic crust - Robador, Alberto; Jungbluth, Sean P.; LaRowe, Douglas E.; Bowers, Robert M.; Rappé, Michael S.; Amend, Jan P.; Cowen, James P. (Frontiers in Microbiology, 2015)
The basaltic ocean crust is the largest aquifer system on Earth, yet the rates of biological activity in this environment are unknown. Low-temperature (<100 °C) fluid samples were investigated from two borehole observatories in the Juan de Fuca Ridge flank, representing a range of upper oceanic basement thermal and geochemical properties. Microbial sulfate reduction rates were measured in laboratory incubations with 35S-sulfate over a range of temperatures, with microbial activity limited by the availability of organic electron donors. Thermodynamic calculations indicate energetic constraints for metabolism in the higher temperature, more altered and isolated fluids, which together with relatively higher cell-specific sulfate reduction rates reveal increased maintenance requirements, consistent with novel species-level dsrAB phylotypes of thermophilic sulfate-reducing microorganisms. Our estimates suggest that microbially-mediated sulfate reduction may account for the removal of organic matter in fluids within the upper oceanic crust and underscore the potential quantitative impact of microbial processes in deep subsurface marine crustal fluids on marine and global biogeochemical carbon cycling.